2003
DOI: 10.1080/1356182031000081740
|View full text |Cite
|
Sign up to set email alerts
|

Of rocks and safe channels: learning to navigate as an interprofessional team

Abstract: A new interprofessional primary care team was established in a greenfield site. Using anethnographic approach, significant experiences in the formation of the team were documented and specific problem areas were defined and addressed using action research principles. The nature of the problems experienced and the processes used in their resolution are described and related to current policy recommendations and to existing literature on the theory and practice of team development. Problems include: the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…For example, some studies found shared objectives to be positively associated with team effectiveness, including measures of patient-centred care and organizational efficiency (Poulton & West, 1999), whilst others found no association between clarity of team objectives and chronic disease management (Hann, Bower, Campbell, Marshall, & Reeves, 2007). In other articles, a shared purpose resulted in an improved ability to identify and resolve problems amongst team members (Bateman, Bailey, & McLellan, 2003) whilst a lack of shared purpose led to anxiety, defensiveness and confrontational relationships within teams (Salhani & Coulter, 2009;Wiles & Robison, 1994). Box 1 highlights a C-M-O configuration for this mechanism.…”
Section: Shared Purposementioning
confidence: 95%
“…For example, some studies found shared objectives to be positively associated with team effectiveness, including measures of patient-centred care and organizational efficiency (Poulton & West, 1999), whilst others found no association between clarity of team objectives and chronic disease management (Hann, Bower, Campbell, Marshall, & Reeves, 2007). In other articles, a shared purpose resulted in an improved ability to identify and resolve problems amongst team members (Bateman, Bailey, & McLellan, 2003) whilst a lack of shared purpose led to anxiety, defensiveness and confrontational relationships within teams (Salhani & Coulter, 2009;Wiles & Robison, 1994). Box 1 highlights a C-M-O configuration for this mechanism.…”
Section: Shared Purposementioning
confidence: 95%
“…Research into protected learning time, [15][16][17] practice-based, small-group learning, 18,19 practice development plans 20 and significant event analysis 21,22 have provided important insights into how and when such tools can be applied to support team learning. 23 Within this literature, there is a growing awareness that team learning is a complex phenomenon [24][25][26] and one that is difficult to effect. [27][28][29][30][31] Perhaps for this reason, there is now some literature directing our attention towards team-learning processes rather than outcomes.…”
Section: Contextmentioning
confidence: 99%
“…Research on practice organisation has tended to focus on interprofessional teamwork,1 – 4 with mainly anecdotal contributions on the relationship between doctors 5. Yet working with other general practitioners has become much the standard in the NHS with its falling numbers of single-handed practices and increases in the size of partnerships, such that nearly a third of general practitioners now work in groups of six or more people 6.…”
Section: Introductionmentioning
confidence: 99%